Sorafenib inhibits cell growth but fails to enhance radio- and chemosensitivity of glioblastoma cell lines - Riedel, Matthias (Oncotarget, 2016)
BACKGROUND: Glioblastomas (GBM) are the most common malignant type of primary brain tumor. GBM are intensively treated with surgery and combined radiochemotherapy using X-irradiation and temozolomide (TMZ) but they are still associated with an extremely poor prognosis, urging for the development of new treatment strategies. To improve the outcome of GBM patients, the small molecule multi-kinase inhibitor sorafenib has moved into focus of recent research. Sorafenib has already been shown to enhance the radio- and radiochemosensitivity of other tumor entities. Whether sorafenib is also able to sensitize GBM cells to radio- and chemotherapy is still an unsolved question which we have addressed in this study. METHODS: The effect of sorafenib on signaling, proliferation, radiosensitivity, chemosensitivity and radiochemosensitivity was analyzed in six glioblastoma cell lines using Western blot, proliferation- and colony formation assays. RESULTS: In half of the cell lines sorafenib clearly inhibited MAPK signaling. We also observed a strong blockage of proliferation, which was, however, not associated with MAPK pathway inhibition. Sorafenib had only minor effects on cell survival when administered alone. Most importantly, sorafenib treatment failed to enhance GBM cell killing by irradiation, TMZ or combined treatment, and instead rather caused resistance in some cell lines. CONCLUSION: Our data suggest that sorafenib treatment may not improve the efficacy of radiochemotherapy in GBM.